Hypo lycemicandhypolipidemic potentials ofalangiumsalviifolium(linn. F). Flowers ethyl acetate extract In streptozotocin induced diabetic rat models - M. SUDHAKAR,; N. SANTAIAH,; J. KAMAKSHAMMA, (International Journal of Pharma and Bio Sciences, 2016)
The present study was carried out to evaluate the hypoglycemic and hypolipidemic activity of ethyl aceteta extract flower extract of Alangium salviifolium (Linn. F). in STZ induced diabetic rats. Diabetes was induced into albino Wistar rats by intraperitonial administration of STZ. Blood samples were collected from overnight fasted normal and diabetic rats on 1th, 5th, 10th and 15th days of treatment. Hypoglycemic activity was evaluated by measuring the serum glucose level and glycosylated haemoglobin level after dosing with ethyl acetate extract. Hypolipidemic activity was evaluated by measuring various biochemical parameter like total cholesterol, triglycerides, low density lipoprotein, very low density lipoprotein, high density lipoprotein and phospholipids. The results showed that the extracts 200 mg/kg and 400 mg/kg significantly (P < 0.001,p<0.01)reduced fasting blood glucose of STZ diabetic rats in a dose-related manner, when compared to control. The ethyl acetate extract has a significant recovery in the levels of parameters measured in lipid profile, when compared to control group. The present investigation established pharmacological evidence to support the folklore claim that it is a hypoglycemic and hypolipidemic agent.